2023
DOI: 10.3390/ijms24076599
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of G Protein-Coupled Receptor Kinase Phosphorylation Sites within the D1 Dopamine Receptor and Their Roles in Modulating β-Arrestin Binding and Activation

Abstract: The D1 dopamine receptor (D1R) is a G protein-coupled receptor that signals through activating adenylyl cyclase and raising intracellular cAMP levels. When activated, the D1R also recruits the scaffolding protein β-arrestin, which promotes receptor desensitization and internalization, as well as additional downstream signaling pathways. These processes are triggered through receptor phosphorylation by G protein-coupled receptor kinases (GRKs), although the precise phosphorylation sites and their role in recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…While some DAR subtypes, such as the D1R [14,15], follow the canonical model of GPCR regulation as described above, the D2R appears to be an exception to this rule. Using site-directed mutagenesis and in situ phosphorylation assays, we previously identified all of the GRK-mediated phosphorylation sites on D2R and, using phosphorylation-deficient receptor mutants, demonstrated that phosphorylation does not regulate D2R interactions with β-arrestin [16,17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…While some DAR subtypes, such as the D1R [14,15], follow the canonical model of GPCR regulation as described above, the D2R appears to be an exception to this rule. Using site-directed mutagenesis and in situ phosphorylation assays, we previously identified all of the GRK-mediated phosphorylation sites on D2R and, using phosphorylation-deficient receptor mutants, demonstrated that phosphorylation does not regulate D2R interactions with β-arrestin [16,17].…”
Section: Introductionmentioning
confidence: 94%
“…Typically, GRK phosphorylation of GPCRs is thought to mediate β-arrestin recruitment, receptor internalization, and downstream signaling pathways [4][5][6]14,37]. Our lab has previously mapped out all the GRK-mediated phosphorylation sites within the D2R [16,17] as well as those mediated by PKCs [38], which together comprise all the sites of known phosphorylation within the D2R when expressed in HEK293 cells.…”
Section: Grks Can Enhance β-Arrestin2 Recruitment To the D2r And Rece...mentioning
confidence: 99%
“…All five DA receptors are GPCRs and interact with arrestins, although the mode of interaction and its functional consequences are unique for each subtype. 17 , 18 , 19 , 20 , 21 , 22 Long-term use of dopaminergic drugs causes persistent changes in DA-dependent behaviors. In rodents with unilateral ablation of the dopaminergic input to the striatum, stimulation with dopaminergic agonists or the DA precursor L-DOPA causes persistent behavioral and molecular sensitization (reviewed in the study by Bastide et al.…”
Section: Introductionmentioning
confidence: 99%